Simultaneous flow cytometric measurement of antigen attachment to phagocytes and phagocytosis. Issue 5 (2nd September 2016) - Laopajon, Witida; Takheaw, Nuchjira; Kasinrerk, Watchara; Pata, Supansa
ABSTRACT: The current available assays cannot differentiate the stages of phagocytosis. We, therefore, established methods for concurrent detection of antigen attachment and engulfment by phagocyte using latex beads coated with lipopolysaccharide, rabbit IgG, and carboxyfluorescein diacetate succinimidyl ester. The generated beads were incubated with whole blood at 37°C for 1 hr and stained with PE-Cy5.5 anti-rabbit IgG antibody. By flow cytometry, attachment and phagocytic processes could be detected, simultaneously. The established method is a valuable tool for diagnosis of phagocytic disorder and study of molecules involved in phagocytosis.